THE ENHANCEMENT OF COMMUNICATION SKILLS AND MASTERY OF CONCEPTS IN SOLUBILITY AND SOLUBILITY PRODUCT LESSON BY LEARNING MODEL OF GUIDED INQUIRY - ahmad tohir; nina kadaritna; tasviri efkar (Universitas Lampung, 2012)
The objective of this research is to describe effectiveness of the learning model of guided inquiry in improving communication skills and mastery of concepts in solubility and solubility product lesson. Samples in this research were students of State Senior High School 1 Tumijajar of classes XI Sciences 3 and XI Sciences 4 even semester School Year 2011-2012 that have equal academic abilities. This research used a quasi experiment method with Nonequivalent Control Group Design. Effectiveness of the learning model of guided inquiry was measured by significant differences in control class and experiment class, shown by significant gain. Based on the results of this research, average value of N-gain for communication skills in control and experiment class were 0,59 and 0,66; and the average value of N-gain for mastery of concepts in control and experiment class were 0,39 and 0,55. Hypothesis testing in this research used test two average different with t-test. The hypothesis result test show that class that used learning model of guided inquiry had higher communication skills and mastery of concepts than class with conventional learning model. This indicated that learning model of guided inquiry was effective to improving communication skills and mastery of concepts in solubility and solubility product lesson. Keywords: guided inquiry, communication skills and mastery of concepts